Smart NIR linear and nonlinear optical nanomaterials for cancer theranostics: Prospects in photomedicine. (July 2017) - Liu, Tzu-Ming; Conde, João; Lipiński, Tomasz; Bednarkiewicz, Artur; Huang, Chih-Chia
Graphical abstract: Abstract: Light-based diagnostics and therapy have become indispensable tools in the field of cancer nanomedicine. Various optical imaging modalities with tomographic capability have been developed to visualize cellular and organismic distributions of molecules. Microscopic pharmacokinetics and the tumor-targeting efficacy of nanoscale effectors can now be precisely evaluated. Moreover, phototherapy using intense laser light has been widely used for treating cancers. Using light-active nanoscale effectors, photothermal and photodynamic therapies on superficial tumors can be achieved with low-illumination lasers. Consequently, for the next generation of photo-medical techniques, the use of near infrared (NIR) excitation sources on NIR-activatable nanoparticles may offer deeper light penetration owing to less extensive scattering and absorption by endogenous chromophores in the NIR spectral region. Therefore, treatments and biodetection within higher tissue volumes and with less side effects (e.g. overheating) may be successfully implemented. This comprehensive review covers the state-of-the-art technologies on (a) advanced laser light sources appropriate for deep tissue theranostics, (b) types of laser interactions with pure-NIR and NIR-upconverting nanomaterials, (c) current development of NIR and multi-photon nanoparticles, (d) application fields of NIR nanomaterials in cancer theranostics, and (e) nanotoxicology of NIR nanoscale effectors for cancer treatment.